Analisis Exergy Pada Combustion Chamber Pembangkit Listrik Tenaga Gas Uap (PLTGU) Teluk Lembu 30 MW - Windy Lusia Samosir; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Combustion chamber is one of the main components in the Combined Cycle Power plant (CCPP) that serves as a supplier of heat energy. Then by the system, the thermal energy will be converted into other forms. Combustion chamber is a major cause of irreversibility in the system. Usually, the performance of a component is evaluated by using the first law of thermodynamics (conservation of energy). However, the first law of thermodynamics only assess the quantity of energy consumption. Therefore, exergy analysis is used (based on the second law of thermodynamics is about the entropy changes) which can be studied more deeply about the quality of an energy (energy available; exergy). The aim of this study is to analysze exergy destruction of combustion chamber on Combined Cycle Power Plant (CCPP) 30 MW Teluk Lembu. Exergy analysis on combustion chamber resulting the exergy destruction is 36.46 MW and exergy efficiency is 63.29%.Keywords: combustion chamber, analysis of exergy, exergy destruction, efficiency exergetic